Exploring the effects of extracranial injections of botulinum toxin type A on prolonged intracranial meningeal nociceptors responses to cortical spreading depression in female rats. (October 2019) - Melo-Carrillo, Agustin; Strassman, Andrew M; Schain, Aaron J; Noseda, Rodrigo; Ashina, Sait; Adams, Aubrey; Brin, Mitchell F; Burstein, Rami
Background: Botulinum neurotoxin type A, an FDA-approved prophylactic drug for chronic migraine, is thought to achieve its therapeutic effect through blocking activation of unmyelinated meningeal nociceptors and their downstream communications with myelinated nociceptors and potentially the vasculature and immune cells. Prior investigations to determine botulinum neurotoxin type A effects on meningeal nociceptors were carried out in male rats and tested with stimuli that act outside the blood brain barrier. Here, we sought to explore the effects of extracranial injections of botulinum neurotoxin type A on activation of meningeal nociceptors by cortical spreading depression, an event which occurs inside the blood brain barrier, in female rats. Material and methods: Using single-unit recording, we studied myelinated C- and unmyelinated Aδ-meningeal nociceptors' responses to cortical spreading depression 7–14 days after injection of botulinum neurotoxin type A or saline along calvarial sutures. Results: In female rats, responses to cortical spreading depression were typically more prolonged and, in some cases, began at relatively longer latencies post-cortical spreading depression, than had been observed in previous studies in male rats. Extracranial administration of botulinum neurotoxin type A reduced significantly the prolonged firing of the meningeal nociceptors, in the combined sample of Aδ- and C-fiber, but not their response probability. Discussion: The findings suggest that the mechanism of action by which botulinum neurotoxin type A prevents migraine differ from the one by which calcitonin gene-related peptide monoclonal antibodies prevent migraine and that even when the origin of migraine is central (i.e. in the cortex), a peripherally acting drug can intercept/prevent the headache.